Measuring the vocabulary size of IIUM pre-sessional students - Engku Ibrahim, Engku Haliza; Othman, Khairiah; Sarudin, Isarji; Muhamad, Ainon Jariah (2014)

(untitled)
The last decade has seen an increased interest in the field of second language vocabulary acquisition (SLVA). The findings in SLVA research point to a need to identify learners’ existing vocabulary size to ensure that they achieved the threshold level of vocabulary. The present study aims to measure the vocabulary size of pre-university students at a public university in Malaysia. The receptive and productive vocabulary size tests were administered to 190 students. The results indicate that these pre-university students have yet to achieve the recommended threshold level of vocabulary that is needed to enable them to successfully acquire vocabulary independently. It was also found that there was a strong relationship (r=0.737) between English language proficiency and vocabulary size, statistically significant at p<0.01 level. Students’ performance in receptive and productive vocabulary was also found to be strongly related (r=0.862), statistically significant at p<0.01 level. This study provides the empirical evidence of the importance of guiding students to acquire the threshold level of vocabulary, thus facilitating them with the skills to further develop their vocabulary repertoire independently.